Low thermal budget processing of CdS thin films - Pradeepkumar M.S.; Singh H.V.; Kumar S.; Basu J.; Ahmad M.I. (My University, 2025)
Cadmium Sulfide thin films were deposited on soda-lime glass substrates by chemical bath deposition technique at bath pH varying from 8 to 11. The films were annealed at temperature 120 °C for 5 min using radiative annealing. The best film coverage at thickness ~ 99 nm, with bandgap 2.15 eV and resistivity of 0.5x101 Ωcm was obtained at a bath pH 10. © 2020 Elsevier B.V.